Exploring the Potential of Multi-AI (Artificial Intelligence) Integration as an Islamic Education Learning Media Instrument - Putri, Luqyana Azmiya; Rohmah, Alviani Nur Baiti; Kartikasari, Vika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2024)
The emergence of Artificial Intelligence (AI) in digital technology is seen as a symbol of progress, convenience, and intelligence, but also perceived by some as a source of concern, anxiety, and fear. However, AI can be optimized to support human tasks, including developing learning media for Islamic Religious Education (PAI). Many AI tools are freely accessible, making them highly potential educational resources. This study aims to explore the potential of AI as a tool for developing learning media in the context of Islamic education. This research employs a library research approach, analyzing data through data reduction, display, and conclusion drawing. The findings reveal several AI-based tools suitable for developing learning media, including Google Sites, Quizizz, ChatGPT, and DALL-E 2. Google Sites can be used to create customizable, user-friendly educational websites. Quizizz is an interactive quiz platform, featuring real-time scoring and engagement tools. ChatGPT functions as a medium for brainstorming, providing feedback, and enhancing student learning, though its use requires proper guidance to avoid misuse. Lastly, DALL-E 2 can generate visual content based on textual descriptions. These four tools can be integrated within a single platform—Google Sites—to create a cohesive and interactive learning experience.